Implementation Of International Data Encryption Algorithm (Idea) In Database Security Web-Based - S Giovani, Edwin; Sapri, Sapri; Jumadi, Juju (LPPJPHKI Universitas Dehasen Bengkulu, 2023)
Security and confidentiality of data or information is one of the important aspects of data or information. The issue of security and confidentiality of computer data is important in this information age, especially for SMK Negeri 3 Seluma. Various ways are done to protect the data or information. One of them is by using cryptography with the International Data Encryption Algorithm (IDEA) algorithm. symmetry cryptography created that provides high enough security. The system implementation uses the PHP programming language with the MySql database. The method used in this research is waterfall, this application is designed using UML (Unified Modeling Language). From the analysis and discussion of the research obtained that the encryption results produced by the International Data Encryption Algorithm (IDEA) do not change the plaintext results into ciphertext if the key is greater than or many of the plaintext characters. The result of this research is a software application that is useful for maintaining database security with the International Data Encryption Algorithm (IDEA) method. With this application can be one solution in securing the database.